One-pot cascade transformation of xylose into γ-valerolactone (GVL) over bifunctional Brønsted–Lewis Zr–Al-beta zeolite. Issue 21 (30th September 2016) - Hernández, Blanca; Iglesias, Jose; Morales, Gabriel; Paniagua, Marta; López-Aguado, Clara; García Fierro, José L.; Wolf, Patrick; Hermans, Ive; Melero, Juan A.
Abstract : Bifunctional Brønsted–Lewis, Zr- and Al-containing beta zeolite catalysts prepared by a post-synthetic methodology promote the one-pot production of γ-valerolactone (GVL) from xylose in alcohol media through a cascade process. Abstract : The one-pot conversion of xylose into GVL in 2-propanol has been achieved over bifunctional Zr- and Al-containing beta zeolite catalysts, prepared via a post-synthetic route, possessing both Brønsted and Lewis functionalities. A GVL yield of 35 mol% was obtained at 190 °C after 48 h.